The Position Of Islamic Law In The Positive Law Of Indonesia (Analysis Of The Application Of Islamic Law Provisions In Aspects Of Marriage Through The System Approach) - Hamonangan, Sobardo; Katjong, Kadir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research with the title: The Position of Islamic Law in Indonesian Positive Law (Analysis of the Application of Islamic Law Provisions in the Marriage Aspect Through a Systems Approach aims to determine and explain the position of Islamic Law which is integrated in Indonesian positive law, especially the application of Islamic law provisions in the Marriage legal aspect in Positive Law in Indonesia.This research is a normative legal study, which uses a normative juridical approach, which is an approach to conducting a study and study of the provisions of Islamic law and positive law that applies in relation to the issue of Islamic law in the provisions of Indonesia's positive law in the aspect of marriage.The research results show that the position of Islamic Law in Indonesian Positive Law can be seen from the development of law and the constitution in Indonesia, where the provisions of Islamic law which are adhered to by the majority of the Indonesian population have become a source of law for the development of national law. Several provisions of Islamic law have been integrated into positive law in the Indonesian legal system and have been implemented in a formal juridical manner, including provisions relating to family/marriage law regulated in Law Number 1 of 1974 concerning Marriage, provisions regarding waqf regulated in Law Number 41 of 2004 concerning Waqf, as well as the existence of Religious Court institutions regulated in Law Number 7 of 2004 1989 which was amended by Law Number 3 of 2006, as an institution authorized to resolve problems related to marriage, inheritance and waqf for citizens who embrace the Islamic religion. Furthermore, through a legal system approach, the enactment of Islamic law provisions in positive law is carried out in a formal juridical manner through the formation of legislation that accommodates the provisions of Islamic law. The position of Islamic law in positive law through a legal system approach can be seen in the provisions of Islamic law which have been integrated into positive law in the Indonesian legal system as a national legal system. The provisions of Islamic law in positive law are included as a substantial component, namely provisions that are guided by citizens, especially those who embrace the Islamic religion. As a structural component, it is seen in the existence of the Religious Courts as an institution that has the authority to resolve problems in family law. and the cultural component (legal culture) is the behavior and high legal awareness of the community, especially citizens who embrace the Islamic religion. These three components of the legal system determine the position of Islamic law in the applicable Positive Law.